THE INFLUENCE OF ORGANIZATIONAL CULTURE, MOTIVATION AND SATISFACTION THROUGH COMMITMENT TO EMPLOYEE PERFORMANCE ATTHE EDUCATION AND CULTURE DEPARTMENT OF MALUKU PROVINCE - Samson Laurens (BADATI, 2022)
This study aims to analyze the influence of organizational culture, motivation and job satisfaction through commitment to employee performance at the Education and Culture Office of Maluku Province. This research is an explanatory research conducted for four months, from September to December 2021. The population is 303 people. The sampling technique is a proportional stratified random technique (stratified random sampling). Determination of the number of samples is based on the sample table developed by Issac and Michael, where if the population is 303 people, then at the 95% confidence level, the sample size is 189 people. Analysis of the data used is path analysis. The results showed that the variables of organizational culture, motivation and job satisfaction through organizational commitment simultaneously (simultaneously) had a positive and significant effect on employee performance variables.